The Reading Literacy at SMP Muhammadiyah 23 Lubuk Palas through The Kampus Mengajar 3 Program - Sahlan Tampubolon; Jojor Silalahi; Herlin Munthe; Dedy Irawan; Sinthya Maranatha hr Munthe (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2022)
Kampus Mengajar 2021 is a continuation program of the Pioneer Kampus Mengajar Program which was implemented in 2020 as proof of campus dedication through students to move towards the success of national education in pandemic conditions. The Kampus Mengajar is part of the Kampus Merdeka program which involves students on each campus from various educational backgrounds to assist the teaching and learning process in schools, especially at the elementary level and provide opportunities for them to learn and develop themselves through activities outside the lecture classroom.Indonesia is in need of help from various parties to move synergistically to succeed national education.The Kampus Mengajar aims to provide opportunities for students to learn and develop themselves through activities outside the lecture class, help schools to provide optimal educational services to all students at the elementary level in limited and critical conditions during the pandemic and provide optimal learning opportunities to all students at the elementary level in limited and critical conditions during the pandemic. The results of this program gave a positive response from the parties at SMP Muhammadiyah 23 Lubuk Palas and had a good impact in terms of learning, technology adaptation and school administration.